Identifica????o de pept??deos antimicrobianos atrav??s de predi????es estruturais por meio de Threading e Ab Initio - Silva, ??llan Pires da (2017)
Currently, various bacteria can be harmful to human health. Moreover, with continued use of antibiotics and development of resistance by these microorganisms, many infections became worrying, with no effective treatments available generating the need for development of other fighting molecules. In this context, the antimicrobial peptides (AMPs) have been proposed as an alternative in the control of infections caused by resistant microorganisms. Despite the variation in sequence levels, AMPs may present high structural conservation in specific families, especially peptides stabilized by disulfide bonds. Canonically, the identification of PAMs is by exploitation of bioactive natural extracts and subsequent analysis and purification thereof. In the post genomics era, in turn, identifying PAMs could be made from databases using molecular modeling of peptides in direct search. In this work were selected AMPs without structure in PDB, from antimicrobial peptide database (APD) (http://aps.unmc.edu/AP/main.php). The sequences were pre-filtered, being selected two AMPs (myticin B and MiAMP-2b) of classes described with modifications in disulfide bonds pattern arrangement. Additionally, the original bank was submitted to STPs identification. PredSTP was used as an additional evaluation. After prefiltering phases, a new potential STP (CRS4C-2b) with a new hypothetical structural topology was modelled by QUARK and simulated at 300 ns molecular dynamics, maintaining the initial structure. The methodology was then applied to identify PAMs in the Zantedeschia aethiopica transcriptome where two new potential PAMs were found that were predicted to be active by CAMP. Thus, the two methodologies developed here can be successfully applied in the identification of new PAMs and in the analysis of the structural diversity of antimicrobial families.